Implementasi Dashboard interaktif menggunakan Knowledge Management untuk Monitoring kinerja Penyelesaian kasus pada Polsek Semendawai Suku III - Vingky Nanda Sari; Bosya Perdana; Tata Sutabri (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The performance of investigators in resolving criminal cases is one of the key indicators of police effectiveness. However, the Semendawai Suku III Police Sector still faces challenges in monitoring case resolution due to the lack of an integrated reporting system and minimal documentation of investigators’ knowledge. This study aims to develop an interactive dashboard system based on Knowledge Management to assist in monitoring case resolution performance and support data- and knowledge-based decision-making processes. The research employs the Prototype method, involving several stages: needs analysis, system design, system development, testing, and refinement. The system was developed using the PHP programming language and MySQL database. The implementation results show that the dashboard can display data on criminal reports, case resolutions, and pending cases in an informative and integrated manner. In addition, the knowledge base feature functions as a medium for storing and sharing investigators’ experiences (lesson learned), allowing field knowledge to be reused by other officers when handling similar cases. Overall, the implementation of the interactive dashboard system based on Knowledge Management at the Semendawai Suku III Police Sector successfully improves work efficiency, strengthens the transparency of investigative performance, and builds a foundation for sustainable organizational learning within the police environment.